Correlation analysis between impaired cortical blood flow and plasma vascular cell adhesion molecule-1 levels in patients with cerebral small vessel disease. - CHEN Ju-luo; LIU Lu; MA Pei-qi; WANG Fu-xing; WANG You-meng (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Objective To investigate the correlation between plasma vascular cell adhesion molecule-1 (VCAM 1) levels and cortical regional blood flow impairment in patients with cerebral small vessel disease (CSVD). Methods All 67 patients with CSVD diagnosed and treated in Fu Yang People's Hospital in Anhui from October 2021 to June 2023 were selected, and 55 subjects were selected as the control group. Using 3.0T MRI with 3D arterial spin labeling (3D-ASL) perfusion imaging technology to measure the cerebral blood flow (CBF) in different cortical regions, and the levels of plasma VCAM-1 were measured by enzyme-linked immunosorbent assay (ELISA). Pearson correlation analysis and partial correlation analysis were used to investigate the correlation between plasma VCAM-1 levels and CBF values in each cortical region. Results Correlation analysis showed that plasma VCAM-1 was negatively correlated with CBF value in the left superior temporal gyrus (r = - 0.285, P = 0.021), supramarginal gyrus (r = - 0.250, P = 0.044), insula lobe (r = - 0.270, P = 0.030), medial prefrontal cortex (r = - 0.329, P = 0.008), middle temporal gyrus (r = - 0.282, P = 0.023), paracentral lobule (r = - 0.274, P = 0.027), and in the right middle temporal gyrus (r = - 0.298, P = 0.016), postcentral gyrus (r = - 0.264, P = 0.033), superior temporal gyrus (r = - 0.275, P = 0.027), supramarginal gyrus (r = - 0.293, P = 0.018), insula (r = - 0.255, P = 0.041) in CSVD group, while the CBF value in the left medial prefrontal cortex in CSVD group was significantly lower than that in control group [(33.46 ± 8.27) ml/(min·100 g) vs. (36.56 ± 8.74) ml/(min·100 g); t = - 2.009, P = 0.047]. Conclusions Plasma VCAM-1 of CSVD patients may serve as a serological marker to evaluate local blood flow damage, suggesting that hypertension causes endothelial damage and inflammatory response.